A Comprehensive Analysis of the Serve Reception Zone, Set Zone and Attack Quality of the Top-Level Volleyball Players - Ali Fatahi; Razieh Yousefian Molla; Sotirios Drikos; Shihab Aldin alriyami; Saed Jadidoleslam (Asociación Española de Ciencias del Deporte, 2022)
The game analysis is known as a useful tool for understanding the level of technical-tactical performance of volleyball. As one of the main characteristics of volleyball is defined as the intense relationship between its skills and concluded performance, the present study aimed to perform a comprehensive analysis of the serve reception zone, set zone and attack quality of the top-level volleyball players. The analysis process included reviewing the videos of the games by an experienced scout man who was an expert analyst and specialist in the knowledge of volleyball skills. Initially, during each game video checking, data were collected, and irrelevant/invalid outputs were deleted. Data were exported to the Data Volley special volleyball analysis software. Bivariate associations were assessed for pairs of variables with Pearson's chi-squared tests. Statistical significance was set at p<0.05. Moreover, the effect size was calculated in terms of Crammer's V, with values of <0.1, 0.1 - 0.3 and > 0.5 for small, medium, and large effects respectively. The results showed that there were significant relationships between reception zone with setting zone, setting zone with attack quality as well as reception zone with attack quality. Coaches may consider the relationship between critical skills of volleyball to promote their team performance.